Live birth after artificial insemination using cryopreserved epididymal sperm recovered from the cauda epididymis of slaughtered non-descript bucks in the Philippines - Ocampo, L. C.; DelaRosa, I. C. J.; Lofranco, J. O. C.; Ortiz, J. G. M.; Ocampo, M. B. (International Journal of Agricultural Technology, 2021)
The study determined the viability of cryopreserved epididymal sperm (EpS) to full term pregnancy through AI technique in hormone responsive recipient goats. Cryopreserved EpS with post thaw motility score of ≥20% were used to inseminate estrus-synchronized (ES-AI) and ovulation-synchronized (FT-AI) recipient goats. The ES-AI goats had a mean hormone response rate (HRR) of 55.5% with a Pregnancy rate (PR) of 25% and full term delivery (FTD) rate of 20%. On the other hand, the ovulation synchronized FT-AI goats registered a mean HRR of 75%, with a PR of 58% and FTD rate of 54.2%. The use of either GnRH or Chorionic gonadotropin on day 9 in the FT-AI goats resulted in a mean hormone response rate, pregnancy rate and full term delivery rate of 72.2%, 61.2%, 58.3 % and 78.6%, 54.5% and 54.5%, respectively. These results validated the usefulness of cryopreserved EpS as an alternative source of germplasm for cryopreservation and utilization for offspring production. Moreover, the study can serve as a research platform for germplasm conservation in vitro and in vivo of genetically diverse native ruminant farm animals as well as endangered wildlife ruminants endemic in the Philippines through the use of Assisted Reproductive Technologies (ARTs).